Strategic therapeutic approaches to overcome emerging dual SRC/ABL kinase inhibitors resistances in chronic phase Ph positive chronic myeloid leukemia - Rana, Rajat; Das, Soumadip; Swami, Aravinda; Pon, Doreen; Ramesh, S; Kumar, Sappa Dilip (Asian Journal of Medical Sciences, 2014)
Chronic myeloid leukemia (CML) is a haematopoietic neoplasm with clinically distinct phases and BCR⁄ABL1 oncogene. Imatinib mesylate, a potent inhibitor of BCR-ABL was highly effective in CML but later in-vitro derived cell line with resistance namely BCR-ABL duplication point mutation, P loop mutation, T315I mutation, C helix, SH2 domain, activation loop, C terminal lobe, SRC family kinase activation led to development of Nilotinib. Although it has potential drug targets as BCR-ABL kinase, KIT, PDGFR but has no role in overcoming in Src family kinase. It prompted strategic rational drug design of Dual Src Family Kinase/Abl Inhibitor Dasatinib, active against 15 clinically significant Imatinib resistant BCR-ABL mutations but inactive against T315I mutation. The propensity of Ph+ CML to develop novel mechanism of resistance led designing of rational therapeutic approaches to eradicate minutest residual diseases along with long term resistance risk. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10454 Asian Journal of Medical Sciences Vol.6(1) 2015 8-15